Using narratives to reduce HIV stigma in rural Ecuador: A health education intervention. (June 2022) - Casapulla, Sharon; Gómez-Urrego, Guillermo; Madrid, Claudia; Iles, Chelsea; Keener, Chris; Viola, Jennifer; Sanchez, Alexandra; Orquera, Cristina; Kingori, Caroline
Objective: To determine the efficacy of using a narrative-based intervention to reduce HIV stigma among members of the general public in a rural community in Ecuador. Design: This cross-sectional intervention study involved a convenience sample of 133 participants from Cariamanga, Ecuador. We used a post-test only comparison group design. Setting: The number of adults living with HIV in Ecuador is increasing. Stigma and discrimination are among the greatest barriers to HIV prevention, access to treatment, care and support. Stigma is also associated with negative health outcomes. The study took place in the rural community of Cariamanga, Loja, Ecuador. Method: The intervention included (1) a fact-based presentation, (2) video stories from two individuals living with HIV and (3) a structured group discussion. Data were collected using an HIV Stigma Scale and an HIV Knowledge Assessment. Data were analysed using independent t -test and multivariate analysis of variance (MANOVA). Results: Participants who received the intervention had higher HIV knowledge scores ( p < .001; d = 2.06) and lower stigma scores (0.59) subsequent to the intervention than the comparison group (1.02, p < .001; d = 1.05). Conclusion: This narrative-based educational intervention was effective in reducing HIV-related stigma. Public health practitioners should consider including narratives as a component of future health education interventions aimed at reducing HIV-related stigma.